Exploring Science Students’ Creativity and Critical Thinking Skills through Fluid Learning - Mahbubah, Khoiro; Santoso, Agus; Afiyah, Durrotul (Universitas Islam Negeri (UIN) Mataram, 2025)
Amid rapid technological Development, creative thinking skills are highly sought after. Creativity enables individuals to generate new ideas, find innovative solutions in complex situations, and adapt more easily to change. This study aims to determine the level of creative thinking skills of prospective science teachers through four primary indicators: flexibility of thinking, fluency in generating ideas, originality of ideas, and the ability to elaborate ideas. This study used a quantitative descriptive approach and involved 20 prospective science teachers at Lamongan Islamic University. The research instrument was a Likert-scale questionnaire. Data were analyzed by assigning a score to each statement, followed by descriptive statistics including averages, frequency distributions, percentages, and standard deviations. Furthermore, students' abilities were categorized by score, and creative thinking skills received the highest score on the fluency indicator (81.20%), while flexibility received the lowest (53.40%). For critical thinking skills, indicators of giving building (55.55%) and organizing strategies and explanations of inference skills are in the low category (54.70%). This condition is caused by students' difficulties in generating new ideas or generating various alternative solutions when facing a problem. Therefore, the results of this study are expected to inform educators in developing learning strategies that stimulate the creativity of prospective science teachers, for example, through learning modules that train 21st-century skills, discovery-based approaches, or the use of media that encourage students to be more daring in their creations.